Single‐dose oral azithromycin prophylaxis in planned vaginal delivery for sepsis prevention: A systematic review and meta‐analysis of randomized controlled trials - Crosara, L. F.; Orsini, P. V. B.; Eskandar, K.; Khalil, S. M.; Castilhos, G. S. F.; Strahl, P. A. M.; Milbradt, T. L.; Philip, C. E. (International journal of gynecology and obstetrics, 2024)
Introduction The use of oral azithromycin (AZI) as a preventive measure against postpartum infections of planned vaginal births has garnered a lot of interest in recent years and has been the subject of many randomized controlled trials (RCTs). However, the results from these trials have not been consistent. Therefore, we aim to perform a systematic review and meta‐analysis to determine whether the use of a single‐dose of oral AZI is clinically significant. Methods We systematically searched PubMed, Embase, and Cochrane Central for RCTs from May to June 2023, comparing a single dose of oral AZI with placebo in patients undergoing planned vaginal delivery at a minimum of 28 weeks of gestational age. The main outcomes were puerperal and neonatal sepsis. Statistical analyses were performed using Review Manager 5.4.1 (Cochrane Collaboration). Heterogeneity was assessed with I2 statistics. Results Four RCTs were included (mothers, n = 42 235; newborns n = 42 492). Approximately 49.8% of mothers received a single dose of oral AZI for sepsis prophylaxis. Compared with placebo, AZI significantly reduced the incidence of puerperal sepsis (risk ratio [RR], 0.65 [95% confidence interval (CI), 0.55–0.77]; P < 0.001), mastitis or breast abscess (RR, 0.58 [95% CI, 0.42–0.79]; P < 0.001), endometritis (RR, 0.65 [95% CI, 0.54–0.77]; P < 0.001), wound infection (RR, 0.81 [95% CI, 0.69–0.96]; P = 0.013), infection rate (RR, 0.62 [95% CI, 0.51–0.76]; P < 0.001), and fever (RR, 0.50 [95% CI, 0.28–0.89]; P = 0.018) in mothers. No statistically significant differences were identified between groups regarding maternal all‐cause mortality and the use of prescribed postpartum antibiotics. Similarly, no statistical differences were noted in the neonatal group regarding sepsis, infection rate, and all‐cause mortality. Conclusion AZI appears to be an effective preventive measure against many postpartum infections in mothers but a substantial impact on neonatal outcomes has not yet been conclusively observed. Synopsis Administration of azithromycin has been shown to prevent postpartum infections and sepsis in mothers undergoing vaginal delivery.